2016
DOI: 10.4314/jmbs.v5i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus exposure among blood donors in Ghana

Abstract: Dengue is an urban arbovirus whose aetiologic agent is the flavivirus with four distinct antigen serotypes (DENV-1, DENV-2, DENV-3 and DENV-4) that is transmitted to humans through the bite of the mosquito Aedes aegypti. Ghana is endemic for Aedes aegypti mosquitoes and probably dengue viruses. Due to limited data on dengue virus exposure among Ghanaians, we surveyed 188 healthy adult blood donors for the presence of IgG and IgM antibodies to the four serotypes of dengue. Five milliliters of peripheral blood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A. aegypti , the primary vector of DENV, is hypothesized to have originated from Africa and native tropical or subtropical regions including West Africa. 36 , 38 The presence of DENV-infected A. aegypti (Table 5) is a major epidemic risk factor since it signifies possible local transmission especially in periurban areas. A. albopictus which was imported into Africa from Asia has been rapidly increasing its geographic range and its presence has been detected across Africa.…”
Section: Discussionmentioning
confidence: 99%
“…A. aegypti , the primary vector of DENV, is hypothesized to have originated from Africa and native tropical or subtropical regions including West Africa. 36 , 38 The presence of DENV-infected A. aegypti (Table 5) is a major epidemic risk factor since it signifies possible local transmission especially in periurban areas. A. albopictus which was imported into Africa from Asia has been rapidly increasing its geographic range and its presence has been detected across Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Aedes mosquitoes have been well documented in Ghana and have been implicated for the transmission of yellow fever (13,22). Studies have detected the presence of antibodies and viral RNA of DENV in different localities in Ghana (16,17). This has emphasized the need to investigate and understand the role of Aedes populations in the spread of these diseases in the country, which will inform the formulation of effective and efficient strategies to prevent future outbreaks or mitigate any outbreak that may arise.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ghana has remained free of an outbreak of these diseases despite Aedes aegypti mosquitoes being present in most part of the country (1315). Recent studies have revealed evidence of DENV-2 (Dengue virus serotype-2) antibodies in people suspected to have malaria or visiting the hospital with acute fever symptoms (16,17). The DENV-2 viral RNA was also detected among two children in some localities in urban Accra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies conducted in Ghana over the years, did not detect any outbreaks of these diseases despite the presence of Aedes aegypti mosquitoes in most parts of the country [17][18][19]. There is now evidence of DENV-2 (dengue virus serotype-2) antibodies in persons visiting the hospital with acute fever symptoms [20,21]. DENV-2 viral RNA was also detected among two children in some localities in urban Accra while the patients had had no prior travel history outside of the country.…”
Section: Introductionmentioning
confidence: 99%